Changing big business : the globalisation of the fair trade movement - Hutchens, Anna. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2010)
Uses empirical data to investigate the challenges facing the fair trade movement and develops new approaches to understanding power, governance, and social change across the fields of economics, politics, and development.
Reprint. Originally published: c2009.
Includes bibliographical references (p. 210-228) and index.
oif 21/05/13
Loan
Keywords: Free trade; Anti-globalization movement; Globalization -- Economic aspects